Service providers’ perspectives on youth peer support: the importance of integration and oversight – an interpretive description study in British Columbia, Canada - Skye Pamela Barbic; Courtney Devane; Corey McAuliffe; Emily Jenkins; Kelli Wuerth (BMJ Open)
Objectives Peer support in youth mental health settings holds promise as a developmentally appropriate and impactful initiative; however, research exploring implementation remains limited. To advance the field and strengthen future implementation efforts, the aim of the present study was to generate new understandings about how non-peer service providers working alongside youth peer support workers experience the peer support role in youth mental health settings.Design Guided by interpretive description and tenets of a research community partnership model, semi-structured interviews were conducted with non-peer service providers (n=11) across three integrated youth services centres in British Columbia, Canada, from August to December 2020. Data were analysed inductively using a constant comparative approach to identify and construct themes.Results Participants emphasised integration and supervision of youth peer support workers as essential for successful peer programming within integrated youth services, highlighting three interconnected themes: defining supervisory roles, envisioning role clarity and capacity and governance of youth peer support services.Conclusions Integrated youth services initiatives and peer-led agencies can play key roles—both directly and indirectly—to strengthen the governance and infrastructure of youth peer support.